A Comparision of conventional and laser assisted desensitization techniques for treating dentinal hypersensitivity - Paladugu Devi Navya; Jaiganesh Ramamurthy (Wolters Kluwer Medknow Publications, 2022)
The study's objective was to assess the effectiveness of conventional and laser-assisted desensitization in treating dentinal hypersensitivity (DH). Twenty patients were divided into experimental and control groups. Following scaling, patients in the control group were instructed to utilize desensitization paste; however, after comprehensive scaling, patients in the experimental group received treatment with the erbium, chromium, yttrium, scandium, gallium garnet (Er, Cr: YSGG) laser. Before laser emission, the visual analog scale (VAS) score was obtained for both groups. Postoperative VAS scores were recorded right away, 1 week and 1 month later for the test group, and 1 week and 1 month later for the control group, following the use of desensitizing paste. In comparison to the control group, the Er, Cr: YSGG laser treatment had a substantially higher desensitizing impact right away, according to the data. The variances in the mean VAS scores between baseline and all time periods after treatment for the test group were statistically significant. At any subsequent assessment, there were no discernible variations in plaque index between the test and control groups. The Er, Cr: YSGG laser is found to be more effective than the control group in treating DH within the confines of this investigation.